Assessment of Some Selected Metals from Textile Effluents in Amhara Region Using AAS and ICPOES - Mulugeta, Marye; Tibebe, Dessie (International Journal of Chemistry and Materials Research, 2019)
Heavy metals are some of the common pollutants that are found in industrial wastewaters a variety sources one of them textile industries. In Ethiopia, there are more than fourteen major textile and garment factories. The study of industrial wastewater, it is important to select the appropriate wastewater treatment program. Samples of textile effluents from textile industries found in Amhara Regional State Bahir Dar, Kombolcha, and Debre Brihan textile industries were collected. Heavy metal concentrations effluents were determined using FAAS and ICP-OES. The determined heavy metal concentration of Pd 0.85 to 0.61, As 1.3 to 0.4, Cr 0.08 to 0.03, Zn 2.6 to 0.32 and Mn 0.37 to 0.25 mg/L by FAAS. The determined heavy metals in all textile industries didn’t have significant effluence to environment, but there is a significant difference between FAAS and ICP-OES. The concentration of all the studied heavy metals except Mn were comparable with the WHO and EEPA guideline. This study suggests quick intervention and closes monitoring to arrest and solve the growing environmental pollution.